Authorising geographical knowledge: the development of peer review in The Journal of the Royal Geographical Society, 1830–c.1880. (April 2019) - Newman, Benjamin
Abstract: When the Royal Geographical Society was founded in 1830, its prospectus made a firm commitment to produce a regular journal of the geographic communications it expected to receive. This article examines how submissions from authors were screened by trusted readers before acceptance and hence begins to elucidate the origins of peer review in the discipline's first English language journal. Whilst there has been extensive examination of geographic texts, hitherto there has not been any systematic examination of institutional peer review's governance of geographic knowledge. Historians of science, however, have begun to historicise peer review within scientific fields. This paper adds to these studies, by bringing a discipline on the periphery of science in the nineteenth century into dialogue with the history of peer review. Through detailed assessment of authors' manuscripts and their associated correspondence, this study reflects on the development of mechanisms that authorised geographic knowledge in the society's journal. It further examines how individual reviewers interpreted and practiced the society's procedures. Overall it demonstrates how peer review was central in shaping the geography that appeared in the pages of The Journal of the Royal Geographical Society . Highlights: Provides one of the first accounts of peer review in the history of geography. Explains the Royal Geographical Society's efforts to govern manuscript submissions. Using unpublished correspondence, it shows the discursive practices of peer reviewers. Stresses that peer reviewers actively shaped geography's textual output. Evidences the unwritten rules that governed knowledge in the RGS's journal.